An Architectural Model for Adapting Domain-Specific AOM Applications - Matsumoto, P. M.; Guerra, E. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
An Adaptive Object Model (AOM) is a common architectural style for systems in which classes, attributes, relationships and behaviors of applications are represented as metadata consumed at runtime. This allows them to be very flexible and changeable at runtime not only by programmers, but also by end users, improving system time-to-market. Nevertheless, this flexibility comes with a cost of a greater complexity when developing the system, and therefore one usually uses a bottom-up approach, adding flexibility only when and where it is needed. As a consequence, many AOM applications are tied to the specific domain to which they were developed and this fact makes it difficult to develop and use generic and reusable AOM frameworks that properly handle specific requirements of the AOM architecture. This work presents an architectural model that aims to adapt domain-specific AOM core structures to a common core structure by identifying AOM roles played by each element through custom metadata configuration. By doing this, this model allows the integration of domain-specific AOM applications and AOM frameworks, making it feasible to develop reusable components for the AOM architecture. This model is evaluated by creating an AOM framework and performing a modularity analysis on a case study based on it.